Managing Protected Areas People and Places - Finneran, Niall; Hewlett, Denise; Clarke, Richard (Springer Nature, 2024)
This open access book brings together 16 specially commissioned chapters drawn from a range of different professional-practitioner and academic global perspectives on the importance of the relationship between people and green and blue spaces. It focuses on issues surrounding the importance of natural environments on public health and wellbeing, and the environmental, cultural, and social importance of green and blue spaces that can result through responsible and sustainable adaptive management processes. It explores how the Covid-19 pandemic forced reconsiderations of our relationship with these natural spaces and highlights the important impact of the pace of climate change. While not pretending to have the answers, the stimulating and imaginative contributions embrace rich perspectives drawn from backgrounds as diverse as heritage studies, tourism, conservation, geography, policy formulation, public health, environmental health, research methods, history, literature, art, and theology.